Women–men-joke then and now. Some comments on the German pun - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2015)
In this article an attempt is made to discuss the German joke regarding its assignment to the class of bad jokes in German. The question of what is a pun and what determines that a humorous text can be classified as bad or good is also important and very interesting. No less important are questions about the possibility of breaking all rules and norms, both of linguistic and social natures. These considerations are documented by examples of German jokes; on the one hand Loriot’s texts, texts from “Was guckst du?” and on the other from websites. The question of whether an analysed joke is good or bad still remains open despite all possible classification attempts, because its interpretation is subjective, to be assessed for what it is by the recipient from the outset.